Experimental evaluation of feedback modalities of five telerobotic tasks - Al-Mouhamed, M.; Nazeeruddin, M.; Islam, Shams (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2010)
A distributed telerobotic system is proposed based on a master-arm station that is interconnected by a computer network to a slave-arm station. The distributed telerobotic system is evaluated using a set of teleoperated experiments: 1) peg-in-hole insertion; 2) assembly of a small water pump; 3) operating drawers; 4) pouring of water; and 5) wire wrapping. Direct teleoperation is evaluated using the following schemes: 1) stereo vision; 2) vision and force feedback (VFF); and 3) vision with active compliance (VAC). Space indexing and scaling tools are also used. Operator hand is logically mapped to a remote tool both in position and force. The operator feels the forces that were exerted on the tool as they were exerted on the hand. Extensive experimental analysis showed that mapping of operator hand motion and force feedback (FF) to a convenient tool point reduces the operator mental load and task time due to highly coordinated motion. Stereo vision may solely be used at the cost of large peak forces and extended task time. VFF has nearly equal task time compared to VAC but with a noticeable increase in contact forces. For a large majority of cases, the contact-based tasks that were done using VAC resulted in the least task times and the least contact forces. VAC is superior to VFF, which is better than V. In other words, there is an enormous gain in stability if one removes the bilateral FF channel in teleoperation and relies on a slave-arm active compliance.